2005
DOI: 10.1002/acp.1106
|View full text |Cite
|
Sign up to set email alerts
|

The role of deliberate practice in chess expertise

Abstract: Two large, diverse samples of tournament-rated chess players were asked to estimate the frequency and duration of their engagement in a variety of chess-related activities. Variables representing accumulated time spent on serious study alone, tournament play, and formal instruction were all significant bivariate correlates of chess skill as measured by tournament performance ratings. Multivariate regression analyses revealed that among the activities measured, serious study alone was the strongest predictor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
202
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 8 publications
15
202
1
8
Order By: Relevance
“…Participants in the expert group engaged in fewer trials and had a more permanent improvement in performance for a more challenging skill than did the intermediate group, which suggests that the expert group's practice was more deliberate and of a higher quality and greater efficiency. It is apparent that expert performers accumulate more hours of deliberate practice than do their less expert counterparts (e.g., Charness et al, 2005;de Bruin et al, 2008;Hambrick et al, 2013;, and these differences in the quality of how they practice may further explain why they reach a higher level of attainment than others. However, the approach employed in this study is descriptive in nature, and care should be taken not to infer causality from the differences in practice characteristics observed between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in the expert group engaged in fewer trials and had a more permanent improvement in performance for a more challenging skill than did the intermediate group, which suggests that the expert group's practice was more deliberate and of a higher quality and greater efficiency. It is apparent that expert performers accumulate more hours of deliberate practice than do their less expert counterparts (e.g., Charness et al, 2005;de Bruin et al, 2008;Hambrick et al, 2013;, and these differences in the quality of how they practice may further explain why they reach a higher level of attainment than others. However, the approach employed in this study is descriptive in nature, and care should be taken not to infer causality from the differences in practice characteristics observed between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several other researchers have subsequently provided support for the "monotonic benefits assumption" p. 368) across a variety of domains (e.g., Charness, Tuffiash, Krampe, Reingold, & Vasyukova, 2005;. Moreover, a recent reanalysis of the studies on chess and music showed that the amount of accumulated deliberate practice alone accounted for 30% of the variance in attainment level (Hambrick et al, 2013;see also de Bruin, Smits, Rikers, & Schmidt, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Charness, Krampe, and Mayr (1996) studied the effects on chess performance of age, coaching (which apparently had little effect), and amount of practice. Charness, Tuffiash, Krampe, Reingold, and Vasyukova (2005) also looked at the link between amount of practice and expertise. Charness and Gerchak (1996) aimed to relate some well-known differences in proportions of top chess performers by sex and nationality to differing national participation rates.…”
Section: Some Illustrative Examples Of Research Studies Using Chess Datamentioning
confidence: 99%
“…In studies by Ericsson and others it is estimated that to reach expertise in performance areas such as music and chess one needs about 10000 hours of practice before the age of 20 (21,22,23). Similar theses have been put forward when it comes to sport (24).…”
Section: Scientific Validity and Practical Utilitymentioning
confidence: 86%